Research on the influence of subjective factors on the occurrence of sports injuries in young volleyball players - Huang Yun; Guba, V.P.; Yang Zhi; Rodin, A.V.; Bulykina, L.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the opinions of specialists on the factors determining the occurrence of sports injuries, as well as to propose a rehabilitation programme for the training of volleyball players in youth teams in Russia and China. Methods and structure of the study. The research was conducted in 2021-2024, involving 84 young men participating in the Russian Volleyball Championship (youth league) and 79 players from the Chinese Volleyball Super League (youth teams). The main research method was a questionnaire survey of athletes and the results of medical examinations, which were aimed at studying the factors and causes of sports injuries among volleyball players in youth teams. Results and conclusions. It has been established that the high level of sports injuries among volleyball players in youth teams in Russia and China is due to subjective factors: physical fatigue, incorrect use of technique, poor health, irrational preparatory activities and inattention.